Modeling the Demand for Curly Red Chili Using a Cobb–Douglas Production Function Approach through the Integration of Demographic and Economic Variables - Nuraini, Syarifah; Aliudin, Aliudin; Wibowo, Aris Supriyo (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Curly red chili is a strategic horticultural commodity that plays an important role in household consumption and regional economic stability. In Tangerang City, its demand fluctuates due to changes in prices, income levels, and population growth. As an urban area with a steadily increasing population and rapid development of the culinary sector, Tangerang City has a high dependence on supplies from other regions, making chili demand and prices relatively sensitive to economic factors. This study aims to analyze the response and elasticity of curly red chili demand in Tangerang City. The research uses secondary data with a quantitative approach through the Cobb–Douglas function model to estimate the effects of price, income, population, and consumption on the quantity demanded. The Cobb Douglas model was selected because it allows direct measurement of elasticity and demonstrates the sensitivity of demand to changes in each variable. The results show that all variables simultaneously affect the demand for curly red chili. The elasticity values obtained indicate whether demand is elastic or inelastic, providing useful insights for maintaining price stability and ensuring adequate supply availability.